2011
DOI: 10.1111/j.1600-6143.2010.03363.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Academic Outcomes after Pediatric Liver Transplantation: Functional Outcomes Group (FOG) Results

Abstract: This multi-center study examined prevalence of cognitive and academic delays in children following liver transplant (LT). 144 patients ages 5-7 and 2 years post-LT were recruited through the SPLIT consortium and administered the Wechsler Preschool and Primary Scale of Intelligence, 3rd Edition (WPPSI-III), the Bracken Basic Concept Scale, Revised (BBCS-R), and the Wide Range Achievement Test, 4th edition (WRAT-4). Parents and teachers completed the Behavior Rating Inventory of Executive Function (BRIEF). Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
129
4
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(143 citation statements)
references
References 32 publications
7
129
4
3
Order By: Relevance
“…Further, when compared to school-age children and adolescents with mild to moderate CKD [19], these results are remarkably similar in their scope and manifestation, and the current data extend those findings to include parental ratings of social-behavior, adaptive behavior, and executive functions, along with direct assessment of attention regulation abilities. Finally, when compared to other preschool populations with chronic conditions, such as congental heart disease [25], Type 1 Diabetes [26], Liver Disease [27], and absence epilepsy [28], the level and subtle diffuse nature of the current findings are remarkably similar across preschool samples. At this developmental epoch, the generalized nature of these findings may be associated with the risk for greater difficulties over the course of development, particularly as the chid enters into the formal school-age years, and implicates the need for early identification of such concerns and early intervention.…”
Section: Discussionmentioning
confidence: 66%
“…Further, when compared to school-age children and adolescents with mild to moderate CKD [19], these results are remarkably similar in their scope and manifestation, and the current data extend those findings to include parental ratings of social-behavior, adaptive behavior, and executive functions, along with direct assessment of attention regulation abilities. Finally, when compared to other preschool populations with chronic conditions, such as congental heart disease [25], Type 1 Diabetes [26], Liver Disease [27], and absence epilepsy [28], the level and subtle diffuse nature of the current findings are remarkably similar across preschool samples. At this developmental epoch, the generalized nature of these findings may be associated with the risk for greater difficulties over the course of development, particularly as the chid enters into the formal school-age years, and implicates the need for early identification of such concerns and early intervention.…”
Section: Discussionmentioning
confidence: 66%
“…By comparison, studies of children with epilepsy also show deficits in intellectual functioning: fullscale IQ mean =85.0 (SD=20.7; n=69), verbal IQ mean =86.9 (SD=22.6; n=69), and performance IQ mean =84.5 (SD=19.4; n=69) (30). Prior studies have reported that children with chronic illnesses, such as chronic liver disease (CLD), experienced comparable deficit in intellectual functioning, attention, and executive function, but a significant improvement in IQ scores was observed in children with CLD after transplantation (full-scale IQ mean =94.7; SD=13.5; effect size =20.35; n=134) (31,32). Such deficit in cognitive function may be associated with poorer academic achievement, health literacy, and psychologic wellbeing in children with CLD (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the BRIEF has been used to assess the effects of medications on executive functions in the everyday life of individuals with attention-deficit hyperactivity disorder (ADHD; Biederman et al, 2011;Dupaul et al, 2012;Findling, Ginsberg, Jain, & Gao, 2009;Maziade et al, 2009;Turgay et al, 2010;Yang et al, 2011), Tourette syndrome (Cummings, Singer, Krieger, Miller, & Mahone, 2002), traumatic brain injury (TBI; Beers, Skold, Dixon, & Adelson, 2005), hepatitis C virus (Rodrigue et al, 2011), major depressive disorder (Roth et al, 2012), and hypertension (Lande et al, 2010). It has also been employed to examine outcomes following interventions such as liver transplantation (Sorensen et al, 2011), chemotherapy in breast cancer (Kesler, Kent, & O'Hara, 2011;McDonald, Conroy, Smith, West, & Saykin, 2013), corticosteroid treatment in children with inflammatory bowel disease (Mrakotsky et al, 2013), and family-based intervention in TBI (Wade, Wolfe, Brown, & Pestian, 2005;Wade, Wolfe, & Pestian, 2004). The BRIEF has also been used to evaluation the outcome of cognitive remediation approaches in ADHD (Beck, Hanson, Puffenberger, Benninger, & Benninger, 2010;Hahn-Markowitz, Manor, & Maeir, 2011) and TBI (Toglia, Johnston, Goverover, & Dain, 2010).…”
Section: Intervention Outcomementioning
confidence: 98%